Unsteady MHD slip flow of a ferrofluid over an impulsively stretched vertical surface - S. M. M. EL-Kabeir; E. R. EL-Zahar; M. Modather; R. S. R. Gorla; A. M. Rashad (AIP Advances, 2019)
Investigation of unsteady magnetohydrodynamic (MHD) mixed convective ferrofluid flow over an impulsively stretchable surface is modeled with convective boundary conditions and partial slip impacts. Employing a finite-difference method, the governing non-similar equations are solved computationally. The sway of different considerable parameters on flow and heat transfer are demonstrated in graphical forms and discussed. The results show that the increment in the volume fraction leads to decrease the velocity and the temperature as well as the skin-friction coefficient and Nusselt number. Moreover, in the assisting flow case both the velocity and skin friction coefficient increase as Biot number increases, while they have the opposite behaviour in the opposing flow case. Also, both the temperature and local Nusselt number increase as Biot number increases for assisting and opposing flows.